2017
DOI: 10.1158/1535-7163.mct-15-0634
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated N,N'-Diarylureas As Novel Therapeutic Agents Against Cancer Stem Cells

Abstract: Colorectal cancer (CRC) is the second-leading cause of cancer-related mortality in the United States. Over 50% of patients with CRC will develop local recurrence or distant organ metastasis. Cancer stem cells play a major role in the survival and metastasis of cancer cells. In this study, we examined the effects of novel AMP-activated protein kinase (AMPK) activating compounds on CRC metastatic and stem cell lines as potential candidates for chemotherapy. We found that activation of AMPK by all fluorinated N,N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…ACC and S6 were selected for analysis because they are downstream effectors of AMPKα that are phosphorylated and dephosphorylated, respectively, with AMPKα activation. As expected based on prior work, FND-4b treatment increased levels of pAMPKα in all five cell lines ( Fig 2 ) [27]. Consistent with this result, increases in pACC and decreases in pS6 were also noted.…”
Section: Resultssupporting
confidence: 91%
“…ACC and S6 were selected for analysis because they are downstream effectors of AMPKα that are phosphorylated and dephosphorylated, respectively, with AMPKα activation. As expected based on prior work, FND-4b treatment increased levels of pAMPKα in all five cell lines ( Fig 2 ) [27]. Consistent with this result, increases in pACC and decreases in pS6 were also noted.…”
Section: Resultssupporting
confidence: 91%
“…There is a formal possibility that phosphorylation of eIF2α was consequence of stress induced by the compound rather than activation of parasite eIF2α kinase, as described for mammalian cells 21 . For example, a modified urea derivative was shown to interact with mammalian CXCR2 receptor preventing signaling 43 , and fluorinated 1,3-diarylureas were found to activate AMP-activated protein kinase, inhibiting cell-cycle progression and proliferation in colorectal and stem cells cancers 44 . This, however, is unlikely to occur in T. cruzi as eight closely related analogs (3b, 3n, 3d, 3j, 3k, 3l, 3t and NCPdCPU) which failed to activate mammalian eIF2α kinases also have no activity against parasites 23 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Many canonical AMPK activities lend themselves to AMPK acting as a tumor suppressor, and therefore loss of expression would promote tumorigenesis (Shackelford and Shaw, 2009 ). Recent work has shown that treatment of colorectal cancer cells and breast cancer cells and tissues with a novel AMPK activator (FNDs) induces apoptosis and cancer cell death (Kenlan et al, 2017 ; Johnson et al, 2019 ). But there is also evidence that AMPK is critical for the maintenance of established tumors and could therefore be targeted for anti-cancer therapies in certain contexts.…”
Section: Ampk Implications In Cancermentioning
confidence: 99%